Treatment of patients with tumor/treatment-related hypothalamic obesity in the first two years following surgical treatment or radiotherapy - Müller, Hermann L.; Witte, Julian; Surmann, Bastian; Batram, Manuel; Braegelmann, Kylie; Flume, Mathias; Beckhaus, Julia; Touchot, Nicolas; Friedrich, Carsten (Scientific reports, 2025)
Survivors of sellar/suprasellar tumors involving hypothalamic structures face a risk of impaired quality of life, including tumor- and/or treatment-related hypothalamic obesity (TTR-HO) defined as abnormal weight gain resulting in severe persistent obesity due to physical, tumor- and/or treatment related damage of the hypothalamus. We analyze German claims data to better understand treatment pathways for patients living TTR-HO during the two years following the index surgical treatment. A database algorithm identified patients with TTR-HO in a representative German payer claims database between 2010 and 2021 (n = 5.42 million patients). Claims from 37 patients with TTR-HO were analyzed on a quarterly basis over 2 years. The analysis considered inpatient, outpatient, and prescription data. In the follow-up period, patients with TTR-HO are hospitalized 3.68 times on average; 37% of hospitalizations in year 1 and 31% in year 2 are due to TTR-HO. On average, patients see a general practitioner 12.27 times and various specialists 20.45 times. The need for complex neuroendocrine therapy develops quickly, with most patients having 2–3 neuroendocrine prescriptions in any given quarter. The management of patients with TTR-HO requires frequent inpatient and outpatient visits for tumor follow-up and management of incident comorbidities, and most patients with TTR-HO require intense polytherapy.